Graphene-based materials for energy harvesting at microwave frequencies: a comprehensive review - Cheah, Dennis Yang Shen; Kang, Chia Chao; Jian Ding, Tan; Mohammadmahdi Ariannejad,; Chang, Clifford Choe Wei
Harvesting energy from microwave frequency is one of the key areas of research in the past decade to provide an alternative power source for wireless devices and sensor networks. The increase in the employment of Internet of Things (IoT) devices as well as sensors in order to support technological advancement leads to an increase in the energy demand. This in turn leads to environmental pollution due to the large amount of batteries being disposed. As such, in order to support the current demand for clean and sustainable energy that can reduce environmental pollution, various approaches to reduce the usage of conventional batteries in these systems are being researched. One of the approaches is the usage of the antenna to harvest radio frequency energy. The appearance of graphene-based material further sparked the interest of researchers due to its exciting properties. Therefore, this paper aims to provide a comprehensive review on the advancement of the usage of graphene-based material in the field of harvesting ambient radio frequency energy. Graphene material is first introduced in order to understand its characteristics and properties as a replacement for the conventional copper material. Current state-of-the-art approaches on graphene-based radio frequency energy harvesting systems were then reviewed and compared. The future prospect of graphene-based material in energy harvesting systems was also presented and discussed, shedding light on the future potential areas for research and development.